Effects of plasma treatment on the oxidative stability of vegetable oil containing antioxidants. (1st January 2020) - Na, HeeSun; Mok, ChulKyoon; Lee, JaeHwan
Highlight: Effects of plasma treatment on oxidative stability were determined in bulk oil. 10 min of plasma treatment induced oxidation like 2.5 h of 100 °C or 48 h of 60 °C. Tocopherols in stripped corn oil remained more than in MCT by plasma treatment. 10 μM of α-tocopherol and sesamol had higher antioxidant power than β-carotene. Moisture content decreased significantly after plasma treatment in bulk oil. Abstract: Plasma, the fourth stage of matter, is a partially or wholly ionized state of gas. Degree of lipid oxidation and effects of antioxidants were evaluated in bulk oils at plasma treatment. Significant changes in the conjugated dienoic acid were induced after 10 min of plasma treatment, which corresponded to treatment for 2.5 h at 100 °C and 48 h at 60 °C. Tocopherol stability in the stripped corn oil was significantly higher than that in medium-chain triacylglycerol after the plasma treatment. The antioxidant capacities of 10 μM of α-tocopherol and sesamol were higher than that of β-carotene, and synergistic effects among α-tocopherol, sesamol, and β-carotene were not observed. Added α-tocopherol and sesamol decreased CDA formation by 33 and 30% compared to control samples after plasma treatment. Moisture content in oils decreased significantly about 20% moisture after 6 min plasma treatment. Lipid oxidation could be an important issue in plasma-treated lipid-rich products.